Seed morphology of nineteen Crotalaria L. (Fabaceae) species in Thailand - Ninkaew, Sakuntala; Pornpongrungrueng, Pimwadee; Balslev, Henrik; Chantaranothai, Pranom (Thai Forest Bulletin (Botany), 2017)
Seed morphology of 19 Crotalaria species in Thailand was studied using stereoscopic microscopy and scanning electron microscopy. Five different morphological types are described based on differences in shape, aril, fracture lines, size and seed coat surface. Each type is morphologically described, compared, illustrated, and the taxonomic implications are discussed. A key to identify the different types or some species is presented.